KONTRADIKSI POLITIK IDENTITAS MENJELANG PEMILIHAN UMUM (PEMILU) 2024 - ALIF ANANDIKA PUTRA; ABDUL KAHAR MARANJAYA (Universitas Mahasaraswati K. Mataram, 2023)
Approximately 1 (one) year before the 2024 general election, unusual statements will be very sensitive and can cause political turmoil. The contradiction of identity politics began with the statement of the General Chairman of the Ummat Party in the Rakernas, which immediately received a response from various parties. From the results of the author's search, there is no legislation that absolutely prohibits identity politics. The creation of balance or opposition that causes division is highly dependent on election participants, especially political parties. Then because there is no legislation that prohibits identity politics absolutely, it does not necessarily make identity politics harmless. The handling of the dangers of identity politics is to place identity politics into election regulations, and provide clear limits related to identity politics.